Perma: Scoping and Addressing the Problem of Link and Reference Rot in Legal Citations. (12th June 2014) - Zittrain, Jonathan; Albert, Kendra; Lessig, Lawrence
Abstract: It has become increasingly common for a reader to follow a URL cited in a court opinion or a law review article, only to be met with an error message because the resource has been moved from its original online address. This form of reference rot, commonly referred to as 'linkrot', has arisen from the disconnect between the transience of online materials and the permanence of legal citation, and will only become more prevalent as scholarly materials move online. The present paper*, written by Jonathan Zittrain, Kendra Albert and Lawrence Lessig, explores the pervasiveness of linkrot in academic and legal citations, finding that more than 70% of the URLs within the Harvard Law Review and other journals, and 50% of the URLs within United States Supreme Court opinions, do not link to the originally cited information. In light of these results, a solution is proposed for authors and editors of new scholarship that involves libraries undertaking the distributed, long-term preservation of link contents.